2020
DOI: 10.1515/tnsci-2020-0006
|View full text |Cite
|
Sign up to set email alerts
|

A Moving Residual Limb: Botulinum Toxin to the Rescue

Abstract: AbstractMovement disorders post-amputation are a rare complication and can manifest as the jumping stump phenomenon, a form of peripheral myoclonus. The pathophysiology remains unknown and there is currently no standardized treatment. We describe the case of a 57-year-old male with unremitting stump myoclonus, starting one month after transtibial amputation, in his residual limb without associated phantom or neurological pain. The consequence of the myoclonus was a reduction in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 11 publications
0
15
1
Order By: Relevance
“…9,11 A neuroma can be an ectopic trigger zone, with increasing rate of contractions when local stimulation is applied. 1,9,10,12 However, in our case and in the case presented in the study conducted by Briand et al, 13 the neuroma showed no triggerable electric point, so local treatment was not indicated. Technical upper motor neuron workup in other cases, including brain and spine imaging, sensoryevoked potential, and electroencephalogram, were normal, except for one case with a lacunar infarct in the left anterolateral thalamus, known to be associated with dystonia and tremor.…”
Section: Discussioncontrasting
confidence: 50%
See 3 more Smart Citations
“…9,11 A neuroma can be an ectopic trigger zone, with increasing rate of contractions when local stimulation is applied. 1,9,10,12 However, in our case and in the case presented in the study conducted by Briand et al, 13 the neuroma showed no triggerable electric point, so local treatment was not indicated. Technical upper motor neuron workup in other cases, including brain and spine imaging, sensoryevoked potential, and electroencephalogram, were normal, except for one case with a lacunar infarct in the left anterolateral thalamus, known to be associated with dystonia and tremor.…”
Section: Discussioncontrasting
confidence: 50%
“…14 Electromyography showed (a) rhythmic spontaneous short bursts of several motor unit potentials, myokymic discharges, or was normal. 1,5,7,9,11,13 One case showed a circadian rhythm (symptoms being worse at night) with a highly elevated index for periodic limb movements with reduced sleep efficiency on polysomnography, which is why pramipexole was suggested. 8 Drug treatment seems generally ineffective, as shown in our case.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…17,18 BoT-A is intended for intramuscular, intradetrusor and intradermal use, and has been increasingly used in clinical care for many neural disorders that include spasticity, 19 and other abnormal movement diseases. 20 Therefore, BoT-A is supposed to treat SCI-induced muscle spasticity. The calcium level plays an important role in the spasticity risk 21 and modulates the activity of calcium channel.…”
Section: Introductionmentioning
confidence: 99%